REPRESENTASI MASKULINITAS BOYBAND SHINEE DALAM VIDEO KLIP RING DING DONG MELALUI ANALISIS SEMIOTIKA - M. Adha Al Kodri (Society, 2016)
In the ranks of K-pop industry, boyband group Shinee certainly not unfamiliar anymore. Since it was formed in 2008, they have received many awards in music’s field. One of their single is championed tittled Ring Ding Dong was released digitally on October 14 th 2009.In the video clip of Ring Ding Dong, described a collection of masculine men who dance vigorously. As well as body shape, accessories, and costume that they wear are very supports the actions of their masculine appearance. In other words, In other words, it can be said that the description of the man in the video clip leads to a masculine man with all the attributes of masculinity, but does not leave a gentle attitude, charisma and their prestige.Therefore, if you see this, the important point in this research is to analyze the representations of masculinity in the video clip boyband Shinee Ring Ding Dong through analysis Semiotics. Semiotic models are models that researchers use semiotics of Roland Barthes. Barthes developed two levels of sign (staggered systems) which allows to generates also meanings stratified, namely the level of denotation and connotation.Meanwhile, the results of this study indicate that masculinity is represented by the personnel of Shinee in the video clip Ring Ding Dong is manifold. Some of the scene showed a new concept of masculinity (the concept of “new man”), but some are still a traditional masculinity. When speaking of new concepts of masculinity, it can do a redefinition of the concept of masculinity, namely the concept of masculine brought by the image of the idol appeared in the mass media.